Cardiac autonomic adaptations in elite Spanish soccer players during preseason - Boullosa, D. A.; Abreu, L.; Nakamura, F. Y.; Munoz, V. E.; Dominguez, E.; Leicht, A. S. (International Journal of Sports Physiology and Performance, 2013)
Purpose: The purpose of this study was to evaluate changes in autonomic control of heart rate (HR) and fitness in a group of elite soccer players during the preseason. Methods: Eight professional male soccer players competing in the Spanish First Division were evaluated in July (wk 1) and September (wk 8) with night-time HR variability (HRV) over 4 different days, ultra-short-term HR recovery (HRR) during a small-sided-games session, Yo-Yo Intermittent Recovery test level 1 (Yo-Yo IR1), and a field test for determination of maximum aerobic speed. Results: Players exhibited a greater HRV and a faster ultra-short-term HRR at wk 8, with the players with a lower HRV at wk 1 exhibiting the greatest improvements at wk 8. However, there were unclear improvements in performance parameters, with maximum HR (HRmax) being reduced over the preseason period. This change in HRmax was correlated with the change in short-term HRV parameters (? = 0.829, P = .042). Large correlations were observed among HRV, ultra-short-term HRR, and field performance parameters only at wk 8. Furthermore, the variation (%) of the root-mean-square of successive differences between R-R intervals was increased during the preseason (12.95% ± 15.14% to 29.39% ± 21.93%, P = .013) and significantly correlated (r = .898, P = .006) with Yo-Yo IR1 performance (~2600 ± 786 m) at wk 8. Conclusions: The current results support the appropriateness and practicality of night-time HRV and ultra-short-term HRR for evaluation of autonomic adaptations in professional soccer players, despite the unclear improvements in specific field performance parameters.